Sortable silt paleo-current proxies of sediment core NAP 63 - 1 - Michel Michaelovitch Mahiques; Renata Hanae Nagai; Gilberto Pereira Dias; Rubens César Lopes Figueira (PANGAEA, 2021)
We present sortable silt mean grain size (a proxy for near-bottom current speed) from a sediment core retrieved at the modern core of Intermediate Water Brazil Current (IWBC), that carries Antarctic Intermediate Water (AAIW) to the north spanning the last 80 kyr. The sortable silt was measured using a Malvern Mastersizer 2000 Laser Analyzer and the data presented is the average of three different measurements per sample.